2007
DOI: 10.1016/j.addbeh.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence rates following behavioral treatments for marijuana dependence

Abstract: Previous studies have noted particular difficulty in achieving abstinence among those who are marijuana dependent. The present study employed a dismantling design to determine whether adding contingency management (ContM) to motivational enhancement therapy plus cognitive behavioral therapy (MET+CBT), an intervention used in prior studies of treatment for marijuana dependence, would enhance abstinence outcomes. 240 marijuana dependent participants were recruited via advertisements and assigned to either MET+CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
202
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(211 citation statements)
references
References 47 publications
6
202
2
1
Order By: Relevance
“…One study only included participants who met the DSM criteria (Kadden et al, 2007), while two included participants who consumed cannabis at a certain frequency (Jungerman et al, 2007;Stephens et al, 1994) and one study included individuals without ''severe dependence'' (Sobell et al, 2009). All four studies showed no significant between group differences at posttreatment for cannabis usage outcomes, but showed mixed results for cannabis problems and severity of dependence outcomes, with the same study (Jungerman et al, 2007) showing significant results for each.…”
Section: Cbt Versus Other Interventions (Or Different Cbt Format or Dmentioning
confidence: 98%
See 3 more Smart Citations
“…One study only included participants who met the DSM criteria (Kadden et al, 2007), while two included participants who consumed cannabis at a certain frequency (Jungerman et al, 2007;Stephens et al, 1994) and one study included individuals without ''severe dependence'' (Sobell et al, 2009). All four studies showed no significant between group differences at posttreatment for cannabis usage outcomes, but showed mixed results for cannabis problems and severity of dependence outcomes, with the same study (Jungerman et al, 2007) showing significant results for each.…”
Section: Cbt Versus Other Interventions (Or Different Cbt Format or Dmentioning
confidence: 98%
“…The same study also identified significant differences for dependence symptoms outcomes. Two studies reported average number of sessions attended across both study groups, reporting 76% (Stephens et al, 1994) and 58% (Kadden et al, 2007) attendance, with no significant differences between groups. At later follow-up points, no significant differences were identified for any key outcomes at 14 or 15 months.…”
Section: Cbt Versus Other Interventions (Or Different Cbt Format or Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, ∼ 24% of patients entering treatment for substance abuse have a diagnosis of cannabis use disorder (CUD;SAMHSA, 2012), yet few patients are able to achieve continued abstinence (Marijuana Treatment Project Research Group, 2004;Budney et al, 2006;Kadden et al, 2007;Levin et al, 2011;Weinstein et al, 2014). There is thus a clear and pressing need to improve treatment outcomes for cannabis use disorder, and pharmacological options are one important strategy needing development.…”
Section: Introductionmentioning
confidence: 99%